Ecological and Human Health Risk Assessment. (1st October 2018) - Charabi, Yassine; Choudri, B.S.; Ahmed, Mushtaque
Abstract : The review of literature in this paper includes the assessment of risk process and addresses issues of both human as well as ecological receptors. The main objective of this review is to highlight an overview of the scientific research literature published in year 2017. The review is focused on assessment of risk on human and ecology published in the literature such as analysis, methodology, interpretation, management, uncertainty, policy and regulatory guidance. The review on ecological and human health risk assessment is divided into two main sections namely ecological and human health. The focus of the review is on the risk assessment process as it is applied to human health, ecoological systems, site investigation, aspects of remediation as well as natural resources.